2019
DOI: 10.21608/zjar.2019.33397
|View full text |Cite
|
Sign up to set email alerts
|

Innovation of Jam From Gurma Melon Pulp as Un Traditional Source

Abstract: Gurma melon (Nubian or Seed melon) Citrullus lantus var. colocynthoides, became an important crop in Egypt. It was cultivated for seeds only, while the residue of fruits are removed as waste. The main objective of the study is to investigate the possibility of utilization Gurma melon pulp in an economic nutrient food products as jam. The obtained results declared that Gurma melon wastes which represented about 95% of crop contained moisture 94.55%, protein 0.84%, fat 0.19%, crude fiber 0.12%, mineral matter 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The examination of the GMP powder revealed the following values: moisture 13.46%, fat (ether extracts) 2.14%, protein 11.38%, ash 3.85%, and total carbohydrates 69.17%. These findings, however, are generally in line with those of Abdelhady et al [ 11 ], Salama et al [ 12 ] and Korish [ 13 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The examination of the GMP powder revealed the following values: moisture 13.46%, fat (ether extracts) 2.14%, protein 11.38%, ash 3.85%, and total carbohydrates 69.17%. These findings, however, are generally in line with those of Abdelhady et al [ 11 ], Salama et al [ 12 ] and Korish [ 13 ].…”
Section: Resultssupporting
confidence: 92%
“…The seeds are the usable part of the fruit, while the remainder of the deseeded fruits are discarded into the environment, creating environmental issues. This wastage accounts for approximately 95.1% of the total fruit weight (65.35% pulp and 29.75% peel) [ 12 ]. These residues can be used as a source of some important vital compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that, for the RJ treatments, the highest consistency value was obtained with the RJC1 treatment followed by RJC then RJC5 treatments. The results are in accordance with Salama et al (2019), who illustrated that, the consistency of gurma melon jam with 1% cinnamon was more than the consistency of gurma melon jam with 0.5% cinnamon.…”
Section: Consistency Of Red Beetroot Jam and Puree Treatmentssupporting
confidence: 91%